Triclinic modification of di-n-butylbis(2-hydroxybenzoato-κ2O1,O1′)tin(IV) - Seik Weng Ng; Kong Mun Lo; Misni Misran; Reza Reisi (Acta Crystallographica Section E, 2008)
The Sn atom in the title compound, [Sn(C4H9)2(C7H5O3)2], is chelated by the carboxylate groups of 2-hydroxybenzoate liagnds, and exists in a six-coordinate skew-trapezoidal bipyramidal coordination geometry [C—Sn—C = 140.1 (3)°].